Titicut follies [1967] - Wiseman, Frederick (Cambridge, MA : Zipporah Films, 2007)
Filmed at the Massachusetts Correctional Institution, Bridgewater, scenes of the daily life and treatment of the men are interspersed with shots from the inmates' talent show.
film
Keywords: Wiseman, Frederick